ANALISIS KESTABILAN LERENG HIGHWALL MENGGUNAKAN METODE BISHOP SIMPLIFIED PADA PIT 13 PT BELAYAN INTERNASIONAL COAL KECAMATAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA - Muhammad Amin Syam; Heriyanto Heriyanto; Hamzah Umar; Chairul Ikhwan; Mifta Sardilla (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2021)
PT Belayan Internasional Coal is an open-pit system mining company, one of its geotechnical activities is the construction of the slopes. Slope stability analysis used the Bishop Simplified method to obtain the value of the dynamic safety factor (≥ 1,1). Currently, the value of the Safety Factor (FK) is an indicator in determining whether the slope is stable or not. The parameters used in the slope stability analysis are the physical and mechanical properties of the rock, namely weight (ɣ), cohesion value (c), and internal shear angle (∅). From the results of dynamic overall slope calculations, the recommended overall slope is constructed with an individual slope angle of 55°, a bench width of 5 meters, a height of 10 meters, and the number of individual slopes of 8 slopes. This design will produce dimensions of the overall slope with 41° slope angle, 80 meters high, and has a dynamic safety factor value of 1,102 with the water-saturated condition. Thus, the slopes are in stable condition.